The use of hand puppets to increase intrinsic motivation during science learning of 6th and 7th grade learners in Dikgale, Limpopo Province, South Africa : a case study - Potgieter, Annelize; McCabe, R.V.; Potgieter, M. J. (International Journal of Educational Development in Africa, 2018)
One of the most important psychological concepts required for enhanced learning is motivation. This is especially true for science, which is seen by learners as being difficult. This study investigated the motivational changes with regard to studying science and the gender and age differences when using hand puppets in the science classroom. In order to examine this, a 7-week intervention involving the teaching of science by means of hand puppets was conducted in two Grade 6 and two Grade 7 classes in rural-based Dikgale, Limpopo Province, South Africa. The learners’ motivation was assessed in terms of basic psychological needs, intrinsic and extrinsic motivation, with a questionnaire before and after the intervention. Data were analysed using a paired sample ttest, an independent t-test and a MANCOVA. The results show an increase in basic psychological needs and intrinsic motivation, and a decrease in extrinsic motivation for science, after the use of hand puppets. In addition, it appears that there are no gender and age differences regarding motivational change when using hand puppets in science education. It is therefore concluded that hand puppets are a promising teaching method that positively affects the motivation of school learners studying science. Thus it is recommended that further research in the form of an experimental longitudinal design be undertaken to ascertain long-term motivational changes. Keywords: astronomy teaching; hand puppets; science learning; motivational change; intrinsic and extrinsic motivation
International Journal of Educational Development in Africa https://doi.org/10.25159/2312-3540/4507 https://upjournals.co.za/index.php/IJEDA ISSN 2312-3540 (Print) Volume 4 | | 2017–2018 | #4507 | 18 pages
Keywords: Astronomy teaching; Hand puppets; Science learning; Motivational change; Intrinsic; Extrinsic motivation; Astronomy - Study and teaching; Puppet making; Programming by example (Computer science)